Sexual Functions Are Impaired in Males and Females With Chronic Spontaneous and Inducible Urticaria: A Controlled Study - Can, Pelin Kuteyla; Can, Utku (Dermatology Practical & Conceptual, 2025)
Introduction: Sexual dysfunction (SexD) related to chronic dermatologic diseases in women and men were reported in literature, but there are few reports on effects of chronic urticaria (CU) on male and female sexual functions. Objectives: The aim was to investigate prevalence of SexD in women and erectile dysfunction (ED) caused by 2 different CU subtypes. Methods: Our study included 100 patients with CU (60 chronic spontaneous urticaria ([CSU]) and 40 chronic inducible urticaria [CIndU]) and 60 healthy controls. Urticaria activity score 7, urticaria control test, Dermatology Life Quality Index, Beck-Depression Inventory, International Index of Erectile Function (IIEF), and Female Sexual Function Index (FSFI) were assessed in patients and controls. Results: Patients with CSU and CIndU had a higher prevalence of ED (43%, 50% vs 10%) and female SexD than controls (83%, 70% vs 20%). CSU and CIndU patients both had lower FSFI scores than controls (22.1±5.9 and 19.5±8.9 vs control; 29.7±3.4). The IIEF score in men with CSU correlated with lower sexual function. Patients with CIndU had only impaired scores of erectile and orgasmic functions. We found impairment in quality of life (QoL) and long disease duration in women (r=-0.36, r=-0.37; p<0.05) and that depressive symptoms both in men and women with CU is associated with more impairment in sexual function (r=-0.44, r=-0.47; p<0.001). Conclusions: Sexual function is affected in both female and male patients with CSU and CIndU. Given that sexual life is a crucial aspect of QoL, it should be considered when assessing treatment outcomes and disease control.